Sądownictwo radzieckie na Wołyniu i w Galicјi Wschodnieј w latach 1939–1941 - Баран, Володимир Кіндратович; Токарський, Василь Васильович; Baran, Volodymyr K.; Tokarskyi, Vasyl V. (lnstytutu pamięci narodoweј, 2015)
У статті розглядається становлення та розвиток радянського правосуддя на Волині та Східній Галичині в 1939-1941 роках. У ній розкривається поняття "політична справедливість" та значення каральних та репресивних органів влади в радянському тоталітарному суспільстві.

The article reviews the formation and development of Soviet justice in Volyn and Eastern Galicia in 1939–1941. It reveals the notion of ‘political justice’ and significance of punitive and repressive authorities in Soviet totalitarian system. The paper shows the main trends of judicial and extrajudicial executions of Stalinist regime against the public of Volyn and Eastern Galicia, which was treated as socially alien and politically hostile. Following the Red Army entry in Polish eastern provinces, there were numerous instances where Red Army soldiers and KGB servicemen organized lynching against Polish law enforcement officers, gendarmes, officers, village policemen and other ‘counter-revolutionary elements.’ At the beginning of the Soviet rule Western Ukraine experienced systematic political repressions carried out almost exclusively by direct orders of the Interior Commissar of the USSR L. Beria and military tribunals. Later, all parts of the Soviet judiciary were formed in the territories annexed to the USSR: local prosecutors, court presidents were appointed. Department of Justice and the Bar Association were created. In this respect, a significant share of cases on counter-revolutionary crimes was conducted by regional courts who applied various penalties against defendants. The article analyzes the individual stages of the criminal process and presents typical examples of execution of Soviet justice in Volyn and Eastern Galicia. Based on the records of the Soviet Union Supreme Court, People’s Commissariat of Justice and the Prosecuto’s Office, the second half of 1940 was marked by substantial consolidation of punitive policy of the authorities in cases on counterrevolutionary crimes. The operating principle of Special Council of the Soviet Union People’s Commissariat for Internal Affairs as the main instrument of extrajudicial repressions is revealed based on materials of Branch State Archive of the Security Service of Ukraine.
The Soviet Judiciary in the Volhynia and in East Galicia in 1939–1941
Keywords: ii wojna światowa; World War Two; sowietyzacja; sovietization; judiciary; sądownictwo; polityczna jurysdykcja; political justice; Wołyń; Volyn; Galicja Wschodnia; Eastern Galicia